Colchicine for Coronary Artery Disease: A Review - Chen, Tao; Liu, Guihong; Yu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery disease is a serious threat to human health. More and more evidences indicate chronic inflammatory plays a key role in the development of this disease. Inflammation markers are gradually used in the diagnosis and treatment. Although the treatment of coronary heart disease with colchicine is still controversial, more and more studies showed that patients can benefit from this medicine. In this review, we discuss and summarize colchicine on essential pharmacology, anti-inflammatory mechanism of action, and the most important and recent clinical studies. According to these literatures, colchicine possibly will possibly become a new valuable and cheap medicine for the treatment of coronary artery disease.